2018
DOI: 10.12973/iejme/3968
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Students’ Understanding of the Measures of Central Tendency and Attitude towards Statistics in Rural Secondary Schools

Abstract: This research was conducted to assess the level of students' understanding of the measures of central tendency and attitude towards statistics. A survey research was conducted on Tenth Graders in nine secondary rural schools in Sabah, Malaysia. A total of 148 students were sampled using stratified random sampling. Statistical Understanding Test of the Measures of Central Tendency and Survey Attitude towards Statistics questionnaire were used as data collection tools. The data was analyzed descriptively and inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 20 publications
0
13
0
2
Order By: Relevance
“…They previously adapted the SATS instrument called Students' Attitude towards Learning Statistics to investigate the change in 237 eleventh graders' attitudes towards statistics and discovered that the students were slightly more positive at the end of the learning of elementary statistics compared to the beginning of the lesson. Similarly, Saidi and Siew (2019) also discovered a positive attitude towards statistics among the 148 Tenth grade science stream students who studied in a rural district of Sabah, Malaysia as overall, as well as in all of the components in SATS-36, except for the Value component. The students were found to react most positively in the Effort component, followed by Cognitive Competence, Interest, Difficulty, Affect, and Value components.This suggested several matters: students were willing to use more effort to learn statistics and believed in their cognitive ability to understand statistics; students also implied that statistics is not a difficult subject and that they had a high interest in it.…”
Section: Introductionmentioning
confidence: 77%
See 3 more Smart Citations
“…They previously adapted the SATS instrument called Students' Attitude towards Learning Statistics to investigate the change in 237 eleventh graders' attitudes towards statistics and discovered that the students were slightly more positive at the end of the learning of elementary statistics compared to the beginning of the lesson. Similarly, Saidi and Siew (2019) also discovered a positive attitude towards statistics among the 148 Tenth grade science stream students who studied in a rural district of Sabah, Malaysia as overall, as well as in all of the components in SATS-36, except for the Value component. The students were found to react most positively in the Effort component, followed by Cognitive Competence, Interest, Difficulty, Affect, and Value components.This suggested several matters: students were willing to use more effort to learn statistics and believed in their cognitive ability to understand statistics; students also implied that statistics is not a difficult subject and that they had a high interest in it.…”
Section: Introductionmentioning
confidence: 77%
“…Thus, the assessment on the attitude towards statistics should be carried out more comprehensively among the Malaysian secondary school students, since this factor might attribute to this matter. Previously, Saidi and Siew (2019) found that the rural secondary students' attitude towards the effort in learning statistics had significant influence on their understanding of statistical concepts, particularly in the measures of central tendency.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…So, it is determined that a "smart robot" is "a mechanical device that independently perceives the external environment; it recognizes the circumstances in which it works, and it moves independently." At the same time, the law declares the ability of the state to adopt a special legislation regulating the ethical standards for the development of robotics, which developers, manufacturers and users of smart robots must follow [13,17]. Note that South Korean law was the first initiative to develop a strategy for artificial intelligence.…”
Section: Resultsmentioning
confidence: 99%